Pregnancy, Physical Activity and Weight Control to Prevent Obesity and Future Chronic Disease Risk in Both Mother and Child - F. Mottola, Michelle (Current Women's Health Reviews, 2015)
Maternal obesity is accelerating world-wide and may be partly due to excessive gestational weight gain (GWG) and weight retention so that women begin a subsequent pregnancy with extra weight. Excessive GWG has been linked to chronic disease risk in the mother and also to an unhealthy foetal environment with downstream consequences for offspring health with risk for childhood obesity. Weight control during pregnancy and prevention of excessive GWG is an important issue for both mother and developing child. A healthy lifestyle through healthy eating and physical activity are key to prevention. Weight management for non-pregnant individuals has been evaluated for over 30 years, and lessons learned may assist in planning interventions for preventing excessive GWG. Many systematic reviews and meta-analyses analyzing the same studies on GWG report very different results. Recently, 10 intervention trials to prevent excessive GWG were published and only 6 of them were successful. Significant association between maternal exercise and GWG guidelines were reported, however, “one size does not fit all”. The failed trials did not have extra faceto- face sessions, were educational based and adherence was <50%. Accountability, face-to-face exercise sessions, and pedometers may motivate pregnant women to increase step counts to 10,000, which, when combined with nutrition control, prevents excessive GWG. Community walking programs that include family members and children may assist pregnant women of all body mass index categories to overcome potential barriers to promote a healthy lifestyle that will benefit them and their families for weight control and prevention of future chronic disease risk.
Keywords: exercise